Ð¥Ð°Ñ€Ð°ÐºÑ‚ÐµÑ€Ð¸ÑÑ‚Ð¸ÐºÐ° Ð¸Ð¼Ð¼ÑƒÐ½Ð¾Ñ„ÐµÐ½Ð¾Ñ‚Ð¸Ð¿Ð° Ð¸ Ð´Ð¸Ñ„Ñ„ÐµÑ€ÐµÐ½Ñ†Ð¸Ñ€Ð¾Ð²Ð¾Ñ‡Ð½Ð¾Ð³Ð¾ Ð¿Ð¾Ñ‚ÐµÐ½Ñ†Ð¸Ð°Ð»Ð° Ð¼ÐµÐ·ÐµÐ½Ñ…Ð¸Ð¼Ð°Ð»ÑŒÐ½Ñ‹Ñ… ÑÑ‚Ñ€Ð¾Ð¼Ð°Ð»ÑŒÐ½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº ÐºÐ¾ÑÑ‚Ð½Ð¾Ð³Ð¾ Ð¼Ð¾Ð·Ð³Ð° Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð¿Ð¾ÑÐ»Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ - Petrenko, Yu. A.; Skorobogatova, N. G.; Volkova, N. A.; Petrenko, A. Yu. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
Stromal cells derived from adult human bone marrow (BM) after in vitro expansion demonstrate a specific immunophenotype and ability to multilineage differentiation, inherent to mecenchymal stromal cells (MSCs)m. It was established that cryopreservation of human BM MSCs by two-step freezing under protection of 10% DMSO enables to preserve their immunophenotype and ability to induced osteogenic and adipogenic differentiation in vitro.